Pemberdayaan Multimedia Bergereja Pada Pemuda Jemaat GPM Souhuru Melalui Pelatihan Software Easy Worship - Leonardo Petra Refialy; Danny Rande; Gabriela Salhuteru (Universitas Lancang Kuning, 2021)
In the current development of science and technology, many impacts appear in every aspect of life, including the aspect of diversity. The rapid progress of science and technology has also resulted in the church starting to adapt in carrying out services. Youth in the church is a very important element in supporting service activities in the church. Worship in this case is intended as an effort by the church to carry out activities that involve youth groups. The Souhuru GPM congregation in developing services within the congregation has taken advantage of the service by utilizing interactive multimedia to empower young people. Community service activities carried out aim to empower youth in supporting multimedia-based service activities. Community service activities by the team using easy worship software training. In carrying out the activities, the team used the theoretical presentation method, followed by a practicum session (Demo Program) and ended with a test and project evaluation to measure the final competencies achieved by the training participants. The conclusion obtained from the implementation of the activity was that participants were very enthusiastic about the process of running the training activities, participants were able to understand the functions of shortcut items and toolbars in easy worship software and were able to create interactive multimedia projects in easy worship software in accordance with the results expected by the community service team.